Experimental studies on nucleate pool boiling heat transfer to ethanol/MEG/DEG ternary mixture as a new coolant - Sarafraz M.M.; Peyghambarzadeh S.M.; Fazel Alavi S.A. (Chemical Industry and Chemical Engineering Quarterly, 2012)
In this paper, nucleate pool boiling heat transfer coefficient of ternary mixtures of ethanol, monoethylene glycol (MEG) and diethylene glycol (DEG) as a new coolant with higher heat transfer coefficient has been investigated. Therefore, at varied concentrations of MEG and DEG and also at different heat fluxes, pool boiling heat transfer coefficients, have been experimentally measured. Results demonstrated the higher heat transfer coefficient in comparison with Water/MEG/DEG ternary mixture. In particular, at high heat fluxes, for ethanol/MEG/DEG mixture, higher boiling heat transfer coefficient is reported. Besides, experimental data were compared to well-known existing correlations. Results of this comparison express that the most accurate correlation for predicting the heat transfer coefficient of ethanol/MEG/DEG is modified Stephan - Preußer which has been obtained in our earlier work.